2010
DOI: 10.1007/s10695-009-9378-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of P450c17-I (17α-hydroxylase/17,20-lyase) in brain and ovary during gonad development in Cynoglossus semilaevis

Abstract: Cytochrome P450c17 (CYP17, 17a-hydroxylase/17,20-lyase) is a critical enzyme in the production of androgens and estrogens in vertebrates. A 2,469 bp full length cDNA of P450c17-I (CYP17A1) has been isolated from the ovary of half-smooth tongue sole, Cynoglossus semilaevis which encodes 509 amino acids. Additionally, a relatively shorter cDNA (1,742 bp), a likely result of polyadenylation, was also found. The putative P450c17-I enzyme shares high sequence identity with that of the fathead minnow (73%), zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The cDNA samples of tissues from normal fish, V. anguillarum infected fish and control fish were used for CsGLys expression patterns with primers CsGL-RT-F and CsGL-RT-R (Table 1). The expression of 18S rRNA was used as an internal control [25] with primers 18S rRNA-RT-F and 18S rRNA-RT-R (Table 1).…”
Section: Primersmentioning
confidence: 99%
“…The cDNA samples of tissues from normal fish, V. anguillarum infected fish and control fish were used for CsGLys expression patterns with primers CsGL-RT-F and CsGL-RT-R (Table 1). The expression of 18S rRNA was used as an internal control [25] with primers 18S rRNA-RT-F and 18S rRNA-RT-R (Table 1).…”
Section: Primersmentioning
confidence: 99%
“…We confirmed the report of Zhou et al (28) regarding the catalytic selectivity of tilapia P450 17A1 and 17A2 (termed P450c17-I and -II in that paper) in zebrafish. P450 17A1 had also been cloned from zebrafish (55) and sole (56). Because both enzymes are expressed in several teleost fish (28), we presume that the pattern is general in these fish.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Pcc-cyp11a1 and Pcc-star transcripts were significantly higher in hepatopancreas, muscle, and spleen tissues. cyp17a1 transcripts were found in gonads of medaka, tilapia, zebrafish, and barfin flounder (Jin et al, 2012), and transcripts were also found in brain and gonadal tissues of half-smooth tongue-sole (Chen et al, 2010) and in both kidney and gonad tissues of Korean rockfish (Mu et al, 2013). cyp17a1 was found to be a key factor associated with mature oocyte cells, and Pcc-cyp17a1 transcripts were only found in ovary, hepatopancreas, eye, and gill tissues in the present study, which demonstrated that steroidogenic genes were involved in gonadal development of gynogenic Pcc-zp, a female-specific gene associated with ovarian development, was present in ovary tissues before being transported to hepatopancreas tissue (Modig et al, 2006), which contains hepatic-specific and ovarian-specific expression patterns (Wu et al, 2012).…”
Section: Tissue-specific Distribution Of the Target Genesmentioning
confidence: 99%